IDENTIFIKASI PERMASALAHAN MOTORIK KASAR PADA ASPEK BERJALAN ANAK USIA 12-18 BULAN DAN PEMBANDING ANAK SEUSIANYA - Ni Made Sulastri (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Motor development is a physical ability related to the body and daily activities. Motor development which involves physical development will also of course have a big influence on other developments. For this reason, parents must of course pay attention to developments in every phase of their child's development. At the age of 12-18 months, the child will have entered the walking phase, the walking phase begins with the child being able to stand firmly, then being able to walk creeping little by little while holding on, until the child will be able to step his feet from the starting position to another position without falling or falling. can run smoothly. The phase until the child can walk smoothly occurs at 12-18 months. If the child has not reached the phase of walking well in that age range, then it can be said that the child has a delay in walking compared to other children his age. For this reason, this research will focus on motor development in children in the aspect of walking and comparisons with children their age. Data collection methods are observation, interviews and documentation methods. The results of the research show that every child who experiences walking delays will look different from the child's development in age, the age limit for walking ability occurs in the age range of 12-18 months, if at that age the child looks different from children his age then the child can be said to have walking delays . This delay is also triggered by parenting patterns and a lack of stimulation for movement involving the child's motor muscles.